Antianginal treatment and quality of life in patients with chronic coronary heart disease - B. I. Geltser; E. V. Solyanik; E. Ya. Yakukhnaya; Yu. Yu. Karpinskaya; E. L. Shuvalova (Кардиоваскулярная терапия и профилактика)
Aim. To assess the effects of various antianginal nitrate therapy variants on quality of life (QoL) in patients with chronic coronary heart disease (CHD). Material and methods. In total, 259 patients were examined: 153 males (59,1 %) and 106 females (40,9 %); mean age 62,6±3,4 years. All participants had Functional Class II-IV effort angina and received antianginal therapy, QoL was assessed with Health-Related QoL scale. Results. In patients receiving retarded isosorbide-5-mononitrate forms (Group I), total QoL score increased from 3,5±0,3 to 7,4±0,25 during three-month follow-up; in participants receiving isosorbide-5-mononitrate and moderately prolonged isosorbide dinitrate (Group II), it increased from 3,3±0,3 to 6,1±0,2. Conclusion. During three-month follow-up, QoL improved significantly in Group I, and to a lesser extent in Group II.